2005
DOI: 10.1124/dmd.105.004093
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Characterization of the 1a Subfamily of Recombinant Human Udp-Glucuronosyltransferases

Abstract: ABSTRACT:The initial glucuronidation rates were determined for eight recombinant human UDP-glucuronosyltransferases (UGTs) of the 1A subfamily, and the bisubstrate kinetics and inhibition patterns were analyzed. At low substrate concentrations, the reactions followed general ternary complex kinetics, whereas at higher concentrations of both substrates, the reactions were mostly characterized by ternary complex kinetics with substrate inhibition. The glucuronidation of entacapone by UGT1A9 was inhibited by 1-na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
70
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(83 citation statements)
references
References 27 publications
11
70
2
Order By: Relevance
“…UGT1A10 showed an 8-fold higher K m value and a 60-fold lower V max value than UGT1A10. These results suggest that UGT1A9 has the lowest apparent affinity for 4-MU among four UGT1A enzymes, consistent with previous studies (Uchaipichat et al, 2004;Luukkanen et al, 2005;Xiong et al, 2006).…”
Section: Expression Of Wild-type and Mutants Ugt1a9 In Hek293supporting
confidence: 81%
See 1 more Smart Citation
“…UGT1A10 showed an 8-fold higher K m value and a 60-fold lower V max value than UGT1A10. These results suggest that UGT1A9 has the lowest apparent affinity for 4-MU among four UGT1A enzymes, consistent with previous studies (Uchaipichat et al, 2004;Luukkanen et al, 2005;Xiong et al, 2006).…”
Section: Expression Of Wild-type and Mutants Ugt1a9 In Hek293supporting
confidence: 81%
“…Kinetic parameters by UGT1A8 could not be calculated because of the enzyme's low affinity for the substrate. These results suggest that UGT1A9 has the lowest apparent affinity for p-NP among four UGT1A enzymes, consistent with previous studies (Luukkanen et al, 2005;Xiong et al, 2006). Next, the kinetic parameters by wild-type and mutants UGT1A9 expressed in HEK293 cells were determined ( Fig.…”
Section: Expression Of Wild-type and Mutants Ugt1a9 In Hek293supporting
confidence: 72%
“…They stated that the reaction involved a compulsory ordered bi bi mechanism based on analysis of inhibition profiles, in which UDP-Ga was the first binding substrate and entacapone was the second binding substrate. The mechanism of BCP-NG formation, in which the first binding substrate is UDP-Ga and the second binding substrate is BCP, agrees well with the results of Luukkanen et al [24]. The differences of kinetic parameters for BCP and UDP-Ga among animal species are believed to be due to complex reactions caused by species differences of UGT isoforms, so when drug metabolism data obtained from laboratory animals are extrapolated to human, differences in the metabolism of animal species must be taken into consideration.…”
Section: Discussionsupporting
confidence: 82%
“…Luukkanen et al [24] reported that the glucuronidation of entacapone by UGT1A9 was inhibited by 1-naphthol in an entacapone-competitive fashion and was noncompetitive with respect to UDP-Ga. Inhibition by UDP, on the other hand, was noncompetitive with respect to enta-capone and competitive with respect to UDPGA. They stated that the reaction involved a compulsory ordered bi bi mechanism based on analysis of inhibition profiles, in which UDP-Ga was the first binding substrate and entacapone was the second binding substrate.…”
Section: Discussionmentioning
confidence: 99%
“…Microsomal protein (5 μg) from baculovirus-infected Sf9 insect cells, which were engineered to express individual UGT enzymes, was used for all the 1A family proteins. This same set of enzymes has been used in previous studies from our lab and have been show to have a high catalytic capacity for a large variety of compounds, allowing for kinetic analyses be carried out under the optimal conditions for each isoform [23,25,27,28]. UGT2B7 was over-expressed in HK293 cells.…”
Section: Glucuronidation Of Estrogens and Their Hydroxyl Derivatives mentioning
confidence: 99%